Extracellular vesicles rich in HAX1 promote angiogenesis by modulating ITGB6 translation. Issue 5 (6th May 2022) - You, Bo; Pan, Si; Gu, Miao; Zhang, Kaiwen; Xia, Tian; Zhang, Siyu; Chen, Wenhui; Xie, Haijing; Fan, Yue; Yao, Hui; Cheng, Tianyi; Zhang, Panpan; et al.
Abstract: Tumour‐associated angiogenesis plays a critical role in metastasis, the main cause of malignancy‐related death. Extracellular vesicles (EVs) can regulate angiogenesis to participate in tumour metastasis. Our previous study showed that EVs rich in HAX1 are associated with in metastasis of nasopharyngeal carcinoma (NPC). However, the mechanism by which HAX1 of EVs promotes metastasis and angiogenesis is unclear. In this study, we demonstrated that EVs rich in HAX1 promote angiogenesis phenotype by activating the FAK pathway in endothelial cells (ECs) by increasing expression level of ITGB6. The expression level of HAX1 is markedly correlated with microvessel density (MVDs) in NPC and head and neck cancers based on an analysis of IHC. In addition to a series of in vitro cellular analyses, in vivo models revealed that HAX1 was correlated with migration and blood vessel formation of ECs, and metastasis of NPC. Using ribosome profiling, we found that HAX1 regulates the FAK pathway to influence microvessel formation and promote NPC metastasis by enhancing the translation efficiency of ITGB6. Our findings demonstrate that HAX1 can be used as an important biomarker for NPC metastasis, providing a novel basis for antiangiogenesis therapy in clinical settings.